﻿New morphological and biological contributions to adults and immature forms of Pissonotus paraguayensis (Fulgoromorpha, Delphacidae) in wetlands of Argentina - Marino, Ana Maria (2024)
In the search for insects as biological control agents for the water primrose, the delphacid Pissonotus paraguayensis (Delphacidae) was found on Ludwigia grandiflora subsp. hexapetala (Onagraceae) in a wetland of Central East Argentina. The morphology of the unknown females (brachypterous and macropterous) and immature stages are described and illustrated. Adults and nymphs were collected in wetlands of Del Plata River Basin, from Buenos Aires to the northeastern part of Argentina. A rearing methodology was developed to perform biological studies. Both winged forms and structural features of the female genitalia are described for the first time at the genus level. Eggs and immature stages are described and keyed; fifth nymphal instars may be easily recognised by the yellowish colouration, blackish on dorsal of head, thorax and abdomen with conspicuous yellowish pits, ventrally only darkened on base of frons extended to lower level of eyes and dorsal surface of antennomeres I and II, and legs with distinctive black marks at femoro-tibial joint and apex. The geographical distribution is updated, expanding its range into Argentina, making Buenos Aires the southernmost limit of the genus in America. Biological information of the species is also reported here: life cycle, fecundity, oviposition behaviour, and host plant. Field observations showed that P. paraguayensis breeds, feeds, and causes damage to L. g. subsp. hexapetala. This delphacid presents a certain degree of specificity to the Ludwigia species in the Jussiaea section in host specificity tests. More studies are required to test this species as a potential biological control agent.